Democratic good governance: new agenda for change - Joseph, Sarah (2001)
Good governance espouses freedom of information, a strong legal system and efficient administration, backed by political mobilisation of the disadvantaged through movements or political parties. Despite the increasingly individualist premises of state theory, representative democracy still provides avenues for public debate on social issues. The emphasis should thus be on strengthening democratic institution rather than bypassing them through increased individual or governmental interventions. - Reproduced
Keywords: Public administration